An introductory educational session improves medical student knowledge and comfort levels in caring for patients with physical disabilities. Issue 1 (January 2020) - Kirshblum, Steven; Murray, Rachel; Potpally, Nikhil; Foye, Patrick M.; Dyson-Hudson, Trevor; DallaPiazza, Michelle
Abstract: Background: Despite a growing number of people living with disabilities (PWD), many experience health disparities related to access to high quality medical care. Lack of knowledge and low comfort level of medical providers in caring for PWD is a significant barrier and can lead to poor health outcomes. Education of future physicians is an important factor in addressing these health disparities. Objective/Hypothesis: The objective of this study is to assess the knowledge and comfort level of first-year medical students towards PWD before and after a mandatory educational session focused on the health disparities and appropriate care of PWD. We hypothesized that this introductory session would lead to a greater awareness and improved comfort level around caring for PWD. Methods: For the two academic years 2016–2018, we created a mandatory educational session for first-year students consisting of a 30-min lecture followed by discussion of video vignettes and a PWD patient panel. Students completed pre- and post-session surveys that evaluated changes in knowledge and comfort levels around working with PWD, and elicited their feedback. Results: 355 students participated in the educational session and among 278 matched pre- and post-survey responses, we found a significant improvement in knowledge and comfort levels towards encountering PWD. Student feedback was overwhelmingly positive with the PWD panel receiving the highest effectiveness rating. Conclusion: A mandatory educational session for medical students including didactics, videos, and testimonials on caring for PWD improved students' knowledge and comfort levels. Additional research on the long-term effects of early training is needed.